The Electronic Beowulf and digital restoration. - Prescott, A (Literary & Linguistic Computing, 1997)
The Electronic Beowulf is a project edited by Professor Kevin S. Kiernan of the University of Kentucky which is creating an archive of digital images of primary evidence for the transmission of the text of Beowulf. This paper describes the nature of this evidence and the way in which digital imaging technology allows aspects of it to be recorded in a way which would not be feasible with conventional photographic technology. The use of digital technology facilitates the virtual restoration of the Beowulf manuscript in a fashion which is also applicable to other damaged manuscripts.